Cerebrospinal fluid leakage after radioisotope cisternography is not influenced by needle size at lumbar puncture in patients with intracranial hypotension - Takahashi, Koichi (BioMed Central, 2009)
BACKGROUND: Radioisotope (RI) cisternography is considered to be the most important examination for the final diagnosis of intracranial hypotension, typically indicating cerebrospinal fluid (CSF) leakage as RI parathecal activity. Early bladder filling (EBF) of RI is another important finding. However, whether EBF without parathecal activity represents real CSF leakage due to intracranial hypotension or only an epiphenomenon of lumbar puncture causing CSF leak through a needle hole has been questioned. METHODS: To address this issue, we performed quantitative analysis of RI cisternography on 171 patients with suspected intracranial hypotension using different needle sizes (22 G, 23 G and 25 G) and compared RI residual activity in the CSF at different time points after injection. We also analyzed occurrence of early bladder filling and post-lumbar puncture headache. RESULTS: No significant difference in RI residual activity was identified between the 22 G, 23 G and 25 G groups. The incidence of parathecal activity and early bladder filling was not significantly different between groups. The 22 G and 23 G groups had a higher but non-significant incidence of post lumbar headache. CONCLUSION: The results suggest that needle size, at least for 22–25 G, does not affect the results of RI cisternographic diagnostic tests for CSF leakage and bladder filling in intracranial hypotension.